Adaptation in the face of adversity: Decrements and enhancements in children's cognitive control behavior following early caregiving instability. Issue 6 (26th May 2021) - Fields, Andrea; Bloom, Paul A.; VanTieghem, Michelle; Harmon, Chelsea; Choy, Tricia; Camacho, Nicolas L.; Gibson, Lisa; Umbach, Rebecca; Heleniak, Charlotte; Tottenham, Nim
Abstract: Cognitive control is typically described as disrupted following exposure to early caregiving instability. While much of the work within this field has approached cognitive control broadly, evidence from adults retrospectively reporting early‐life instability has shown more nuanced effects on cognitive control, even demonstrating enhancements in certain subdomains. That is, exposure to unstable caregiving may disrupt some areas of cognitive control, yet promote adaptation in others. Here, we investigated three domains of cognitive control in a sample of school‐age children ( N = 275, Age = 6‐12 years) as a function of early caregiving instability, defined as the total number of caregiving switches. Results demonstrated that caregiving instability was associated with reduced response inhibition (Go/No‐Go) and attentional control (Flanker), but enhanced cognitive flexibility (Dimensional Change Card Sort Task Switching). Conversely, there were no statistically significant associations with group (i.e., institutional care versus foster care) or maltreatment exposure and these patterns. These findings build on the specialization framework, suggesting that caregiving instability results in both decrements and enhancements in children's cognitive control, consistent with the hypothesis that cognitive control development is scaffolded by early environmental pressures.